GAMBARAN BAYI BERAT LAHIR RENDAH (BBLR) DI RSUD DR.H.ANDI ABDURRAHMAN NOOR - Wahyuni Wahyuni; Desilestia Dwi Salmarini; Paul Joae Brett Nito (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
In Indonesia, the high death rate for babies with low birth weight in the first month of life in 2013-2018 was 6.2%. LBW will have a long-term impact in the future which will affect the quality of the nation's next generation. Therefore, general management of LBW is very necessary to prevent complications. The aim of this article is to identify the incidence of low birth weight (LBW) babies at Dr.H.Andi Abdurrahman Noor Regional Hospital. The method used is a descriptive quantitative approach. The highest proportion was in the category of Low Birth Weight Babies (LBW) 47.5%, then in the category of Very Low Birth Weight Babies (BBLSR) 35% and Very Very Low Birth Weight Babies (BBLASR) 17.5%. Most of the sample of babies in this study were in the LBW category, born preterm and in the SMK classification.